MORE MORTGAGES, LOWER GROWTH?. (15th October 2015) - Bezemer, Dirk; Grydaki, Maria; Zhang, Lu
Abstract : In newly collected data on 46 economies over 1990–2011, we show that financial development since 1990 was mostly due to growth in credit to real estate and other asset markets, which has a negative growth coefficient. We also distinguish between growth effects of stocks and flows of credit. We find positive growth effects for credit flows to nonfinancial business but not for mortgage and other asset market credit flows. By accounting for the composition of credit stocks and for the effect of credit flows, we explain the insignificant or negative growth effects of financial development in recent times. What was true in the 1960s, 1970s, and 1980s when the field of empirical credit‐growth studies blossomed, is no longer true in the 1990s and 2000s. New bank lending is not primarily to nonfinancial business and financial development may no longer be good for growth. These trends predate the 2008 crisis. They prompt a rethink of the role of banks in the process of economic growth. ( JEL E44, O16, O40, C33)